Solid Waste Management in Libya: Challenges and Sustainable Solutions (City of Al-Abyar as a Case Study) (Sebha University Conference Proceedings, 2024)
The study aimed to analyze the current situation of solid waste management in the city of Al-Abyar, identify the main challenges facing the waste management system in the city, explore possible sustainable solutions to improve waste management in Al-Abyar, and provide practical recommendations for local authorities and relevant stakeholders to enhance the efficiency and effectiveness of waste management. The study employed a descriptive-analytical approach using a questionnaire as a tool for data collection. A sample of 396 residents from Al-Abyar was selected. The study concluded that the waste disposal sites in the city are not adequately suitable, causing significant environmental problems due to the pollution they generate. Solid waste management in Al-Abyar requires substantial improvements, particularly in the areas of recycling, community awareness, and legislation and policies. The study recommended developing and improving waste disposal sites to be located away from residential areas and equipped with treatment systems to reduce pollution. It emphasized the necessity of adopting an integrated framework for waste management that includes improving infrastructure, enhancing recycling programs, increasing community awareness, and improving legislation and policies to achieve sustainable and effective solid waste management in Al-Abyar.